FIGURATIVE LANGUAGE USED BY THE ENGLISH TEACHER IN EFL CLASSROOM AT SMA NEGERI 1 TORAJA UTARA (LPPM UKI Toraja, 2020)
This research aims at to find out the types of figurative language used by the English teacher in EFL classroom at SMA Negeri 1 Toraja Utara, and the dominant of figurative language used by the English teacher in EFL classroom at SMA Negeri 1 Toraja Utara. The researcher in this study use qualitative research design. The subject of this research is one of English Teacher at SMA Negeri 1 Toraja Utara. The result of the research revealed that there are 8 types of Figurative Language used by the English teacher and some of types of figurative language use more than one, they are: 3 Rhetoric, 9 Repetition, 4 Metonymy, 4 Ellipsis, 2 Irony, 2 Personification, 1 Pleonasm, 1 Simile, the total of all are 26 types of figurative language and the mostdominant of figurative language used by the English teacher is Repetition. By this result of the research, the researcher suggest that the in teaching process the teacher needs to be more creative expressive in communicating to students, in order that the students be more engaged in studying.